2022
DOI: 10.3390/nu14122370
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physical Activity Differences Due to COVID-19 Pandemic Lockdown on Non-Alcoholic Fatty Liver Parameters in Adults with Metabolic Syndrome

Abstract: Background: A Mediterranean lifestyle with a Mediterranean diet and regular physical activity (PA) improves metabolic syndrome (MetS) characteristics and non-alcoholic fatty liver disease (NAFLD). The COVID-19 pandemic stopped healthy habits and increased NAFLD progression. Objectives: To assess how PA differences due to COVID-19 lockdown affected NAFLD parameters in adults with MetS. Design: Longitudinal 2-year analysis of data obtained between COVID-19 pre- and post-lockdown in a parallel-group randomized tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Regular physical exercise is known to lead to more favorable metabolic profiles and reduction in the levels of the biomarkers of inflammation and liver status [ 50 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. Physical activity may also play a role in regulating the status of inflammation and oxidative stress [ 35 , 50 , 96 , 97 ]. In obese individuals, liver enzyme activities have been shown to correlate with the degree of fat deposition and to decline with losing weight.…”
Section: Discussionmentioning
confidence: 99%
“…Regular physical exercise is known to lead to more favorable metabolic profiles and reduction in the levels of the biomarkers of inflammation and liver status [ 50 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. Physical activity may also play a role in regulating the status of inflammation and oxidative stress [ 35 , 50 , 96 , 97 ]. In obese individuals, liver enzyme activities have been shown to correlate with the degree of fat deposition and to decline with losing weight.…”
Section: Discussionmentioning
confidence: 99%
“…Taking physical exercise in a regular manner as part of treatment protocols may be expected to lead to more favorable metabolic profiles with associated reduction in the levels of predictive biomarkers of health [ 18 , 24 , 57 , 58 ]. Physical activity seems to play a role in correct maintenance of GGT enzyme, which based on previous observations can be considered a marker of oxidative stress and a mechanistic link between hepatic and extrahepatic disease manifestations due to its pathogenic role in LDL oxidation in coronary arteries [ 57 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The average fatty liver index (FLI) as a surrogate for NAFLD increased from 25.2 to 33 in this study[ 73 ]. Another Spanish study showed a decrease in physical activity during lockdown with a consecutive increase in FLI and worsening of metabolic status[ 74 ]. In an Italian cohort study, 48% of 357 NAFLD patients gained weight during lockdown, and this weight gain was associated with abandonment of a Mediterranean diet and decreased physical activity in univariate analysis and various multivariate models.…”
Section: Influence Of Epidemic Hygienic Covid-19 Measures On Nafldmentioning
confidence: 99%